Maternal sildenafil for severe fetal growth restriction (STRIDER): a multicentre, randomised, placebo-controlled, double-blind trial. (February 2018) - Sharp, Andrew; Cornforth, Christine; Jackson, Richard; Harrold, Jane; Turner, Mark A; Kenny, Louise C; Baker, Philip N; Johnstone, Edward D; Khalil, Asma; von Dadelszen, Peter; Papageorghiou, Aris T; Alfirevic, Zarko; et al.
Summary: Background: Severe early-onset fetal growth restriction can lead to a range of adverse outcomes including fetal or neonatal death, neurodisability, and lifelong risks to the health of the affected child. Sildenafil, a phosphodiesterase type 5 inhibitor, potentiates the actions of nitric oxide, which leads to vasodilatation of the uterine vessels and might improve fetal growth in utero. Methods: We did this superiority, placebo-controlled randomised trial in 19 fetal medicine units in the UK. We used random computer allocation (1:1) to assign women with singleton pregnancies between 22 weeks and 0 days' gestation and 29 weeks and 6 days' gestation and severe early-onset fetal growth restriction to receive either sildenafil 25 mg three times daily or placebo until 32 weeks and 0 days' gestation or delivery. We stratified women by site and by their gestational age at randomisation (before week 26 and 0 days or at week 26 and 0 days or later). We defined fetal growth restriction as a combination of estimated fetal weight or abdominal circumference below tenth percentile and absent or reversed end-diastolic blood flow in the umbilical artery on Doppler velocimetry. The primary outcome was the time from randomisation to delivery, measured in days. This study is registered with BioMed Central, number ISRCTN 39133303. Findings: Between Nov 21, 2014, and July 6, 2016, we recruited 135 women and randomly assigned 70 women to sildenafil and 65 women to placebo. We found no difference in the median randomisation to delivery interval between women assigned to sildenafil (17 days [IQR 7–24]) and women assigned to placebo (18 days [8–28]; p=0·23). Livebirths (relative risk [RR] 1·06, 95% CI 0·84 to 1·33; p=0·62), fetal deaths (0·89, 0·54 to 1·45; p=0·64), neonatal deaths (1·33, 0·54 to 3·28; p=0·53), and birthweight (−14 g, –100 to 126; p=0·81) did not differ between groups. No differences were found for any other secondary outcomes. Eight serious adverse events were reported during the course of the study (six in the placebo group and two in the sildenafil group); none of these were attributed to sildenafil. Interpretation: Sildenafil did not prolong pregnancy or improve pregnancy outcomes in severe early-onset fetal growth restriction and therefore it should not be prescribed for this indication outside of research studies with explicit participants' consent. Funding: National Institute for Health Research and Medical Research Council.